(untitled) (International journal of medical sciences, 2026)
Celiac disease is a chronic autoimmune disorder triggered by gluten ingestion in genetically predisposed individuals. The disease affects the small intestine and leads to malabsorption of nutrients due to immune-mediated damage of the intestinal mucosa. Recent advances in laboratory and instrumental diagnostic techniques have significantly improved the early detection and clinical management of this condition. The present article analyzes modern diagnostic methods of celiac disease, including serological testing, genetic analysis, and histological examination of intestinal biopsies. The clinical significance of early diagnosis and its impact on preventing complications such as anemia, osteoporosis, infertility, and intestinal lymphoma are also discussed. The article is based on data from international medical literature and clinical studies. Modern diagnostic approaches play an important role in the timely identification of patients with celiac disease and contribute to improving the quality of life of affected individuals through early dietary intervention.